Nomina Bahasa Mongondow dalam Tuturan Masyarakat di Desa Lolak: Penelitian - Martiana Paputungan; Zakaria, Ulfa; Wa Ode Irawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study discusses the noun word class with the aim of describing the form and formation of Mongondow language nouns in the speech of the people in Lolak Village. The method used is descriptive qualitative with data sources from active speakers in the Lolak Village community. Data collection techniques include interviews, listening, taking notes, recording, and speaking. The data analysis techniques used in this study are data reduction, presenting data in the form of tables and descriptions to make it easier to understand the form of Mongondow language nouns in the speech of the people in Lolak Village and concluding the results of the analysis. This study concludes that the process of forming derived nouns through several types of word classes while basic nouns can stand alone.